Modeling, Analysis and Design of Feedback Operational Amplifier for Undergraduate Studies in Electrical Engineering - Han Yang (Institute of Advanced Engineering and Science, 2012)
The analog electronics is a challenging subject for undergraduate students in electrical engineering, due to the complex combination of many previous subjects, such as linear circuit analysis, signal and system, linear control theory and some sort of mathematics. This paper presents the modeling, analysis and design of the operational amplifier, which is used as benchmark system for analog electronics, for undergraduate studies in electrical engineering. Followed by the introduction of the operation amplifier circuit, the design of feedback network for the operational amplifier using MATLAB is presented. The bandwidth and sensitivity analysis for the feedback control loop are also discussed. In order to enhance the stability margin and dynamic characteristics of the operational amplifier, the lead compensator is designed for the feedback loop by adding capacitive component to the feedback resistive network. The presented analysis and design method of the operational amplifier by using MATLAB/SIMULINK can be highly effective to compliment the classroom teaching for circuit design courses for undergraduate studies in electrical engineering. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1609